X-Slot microstrip patch antenna for Sub-6 Ghz 5G router applications - Amir Farhan, Asri; Mohd Hisyam, Mohd Ariff; Mohammad Fadhil, Abas; Nor Hadzfizah, Mohd Radi; Nurulfadzilah, Hasan; Rahimah, Jusoh (IEEE Xplore, 2025)
The development of a microstrip antenna for 5G router applications is presented in this research. The rectangular shape of the suggested antenna includes a partial ground plane and X slot at the patch. The antenna is made to function at the 3 GHz to 5 GHz wideband frequency that cover Malaysia's 3.5 GHz (5G Band n78) system with gain of 2.44 dBi and bandwidth of 2 GHz. Additionally included are the outcomes of various antenna characteristics, including radiation pattern, gain, bandwidth, Return Loss (S11), and Voltage Standing Wave Ratio (VSWR). CST Studio Suite 2021 is used to examine the antenna simulation. The suggested antenna measures 50 mm by 50 mm by 1.6 mm overall. This antenna also covers n77 and n79 for Sub-6 GHz 5G New Radio frequency bands. The recommended antenna also has a low profile, a straightforward structure, and is simple to fabricate.